Hubungan Tingkat Pengetahuan Ibu Tentang Asi Eksklusif Dengan Tindakan Pemberian Asi Eksklusif Di Puskesmas Kartasura - Ilhami, Muhammad Fadhil, dr. Burhanudin Ichsan, M.Med,Ed.,M.Kes, dr. Dodik Nursanto (2015)
Background : Exclusive breastfeeding is defined as no other food or drink, not even water, milk or formula, except breast milk. Breast mik are also high quality nutrients and quality of all time. At present, breastfeeding is recommended for at least the first 6 months of life. This study aimed to determine the relationship between maternal knowledge with action exclusive breastfeeding. Methods : the study design was obsevational analytic cross-sectional approach. The number of respondents were 72 mothers who were selected using cluster random sampling technique. Chi-Square test is used to determine the relationship between maternal knowledge with action exclusive breastfeeding. Results : Mother with low knowledge are 44 people (61.1%) and the high knowledge are 28 people (38.9%). Mothers with high knowledge with good action are 24 people (85,7%) and the low knowledge with good action are 21 people (47,7%). Statistical analysis showed the value of p =0,001. Conclusion : There is significant relationship between maternal knowledge with action exclusive breastfeeding in the health centers of Kartasura.